Global comparison of the economic costs of coronary heart disease: a systematic review and meta-analysis - Lan Gao; Susan Brumby; Crystal Man Ying Lee; George Mnatzaganian; Suzanne Robinson; Helen Brown; Rachel Huxley; Anna Peeters; Dan Xu; James Boyd; Sean Randall; Adrienne O’Neil; et al. (BMJ Open)
Objectives Coronary heart disease (CHD) is the leading cause of global morbidity and mortality, yet no comprehensive evaluation of its global economic costs exists. We conducted a systematic review with meta-analysis to examine the costs of CHD treatment by region and CHD subtypes, examine whether there are cost difference by sex, and examine costing methodologies.Design We conducted a systematic review and meta-analysis of non-randomised studies.Data sources We searched Medline, Embase, CINAHL, EconLit and Google Scholar from 1 January 2000 to February 2023.Eligibility criteria for selecting studies We included observational studies reporting economic costs of CHD treatment and outcomes for adults that were published in English.Data extraction and synthesis Data extraction and quality assessment were independently undertaken by two reviewers. Costs were converted to percentage of gross domestic product (GDP) per capita of corresponding country. A random-effects model was used for meta-analysis using StataSE V.18 to calculate the pooled percentage. Heterogeneity was assessed using the I2 statistic. Meta-regression and bias assessment were performed.Results Out of 20 100 records identified, 37 studies (including 2 564 189 individuals) from 22 countries were included in the qualitative synthesis and the quantitative meta-analysis. In most countries, the annual cost of CHD exceeds many times the total health expenditure per capita. The pooled direct annual cost of CHD per patient varied from 4.9% to 137.8% of GDP per capita (Int$ purchasing power parity), with pooled percentage of 21.7% (95% CI 15.3, 28.1) for those with CHD. Slight difference in the annual pooled cost of CHD was observed, with a 2% of GDP per capita higher cost in men (95% CI 0.8, 3.2). Most studies applied a top-down costing approach (n=21).Conclusions The review illustrates the expense associated with CHD, which is varied by region and CHD subtypes. The observed cost difference by sex warrants further exploration of sex-specific factors influencing cost disparities. Exploring advanced costing methods such as time-driven activity-based costing can optimise resource allocation and identify opportunities to reduce unnecessary costs and cost disparities.PROSPERO registration number CRD42023412044.